Por uma história do desenvolvimento - dos Santos, Moacir José [UNESP]; Carniello, Monica Franchi (My University, 2011)
This paper proposes a discussion on the need to prepare a history of development through effective approaches and methods of its own history. The objective is to show how, until now, historians have not produced a history of development in light of the discussions and disputes related to the structuring of history as a field of knowledge. To this end, it was demonstrated how history can help to identify the borders of history that allowed the consecration of a limited development model and tied only to criteria of economic performance.
For a history of development
Keywords: History; History of the development; Interdisciplinary